Evaluation of early-phase [18F]-florbetaben PET acquisition in clinical routine cases - Daerr, Sonja; Brendel, Matthias; Zach, Christian; Mille, Erik; Schilling, Dorothee; Zacherl, Mathias Johannes; Bürger, Katharina; Danek, Adrian; Pogarell, Oliver; Schildan, Andreas; Patt, Marianne; Barthel, Henryk; et al. (NeuroImage clinical, 2017)
In recent years several [18F]-labelled amyloid PET tracers have been developed and have obtained clinical approval. There is accumulating evidence that early (post injection) acquisitions with these tracers are equally informative as conventional blood flow and metabolism studies for diagnosis of Alzheimer's disease, but there have been few side-by-side studies. Therefore, we investigated the performance of early acquisitions of [18F]-florbetaben (FBB) PET compared to [18F]-fluorodeoxyglucose (FDG) PET in a clinical setting. All subjects were recruited with clinical suspicion of dementia due to neurodegenerative disease. FDG PET was undertaken by conventional methods, and amyloid PET was performed with FBB, with early recordings for the initial 10min (early-phase FBB), and late recordings at 90–110min p.i. (late-phase FBB). Regional SUVR with cerebellar and global mean normalization were calculated for early-phase FBB and FDG PET. Pearson correlation coefficients between FDG and early-phase FBB were calculated for predefined cortical brain regions. Furthermore, a visual interpretation of disease pattern using 3-dimensional stereotactic surface projections (3D-SSP) was performed, with assessment of intra-reader agreement. Among a total of 33 patients (mean age 67.5±11.0years) included in the study, 18 were visually rated amyloid-positive, and 15 amyloid-negative based on late-phase FBB scans. Correlation coefficients for early-phase FBB vs. FDG scans displayed excellent agreement in all target brain regions for global mean normalization. Cerebellar normalization gave strong, but significantly lower correlations. 3D representations of early-phase FBB visually resembled the corresponding FDG PET images, irrespective of the amyloid-status of the late FBB scans. Early-phase FBB acquisitions correlate on a relative quantitative and visual level with FDG PET scans, irrespective of the amyloid plaque density assessed in late FBB imaging. Thus, early-phase FBB uptake depicts a metabolism-like image, suggesting it as a valid surrogate marker for synaptic dysfunction, which could ultimately circumvent the need for additional FDG PET investigation in diagnosis of dementia. •Early-phase [18F]-florbetaben uptake depicts a metabolism-like image•Strong relative quantitative and visual correlations of early-phase [18F]-florbetaben uptake with FDG images•A two-phase [18F]-florbetaben protocol might give combined neurodegeneration and amyloid pathology biomarker information•Early-phase [18F]-florbetaben PET could ultimately circumvent the need for an additional FDG-PET in the dementia work-up.